Adição de cinzas do bagaço da cana-de-açúcar em compósitos cimentícios reforçados com fibras de sisal - Secchi, Maicon (2018)
Portland cement is the second material most used by humans. Exorbitant energy is consumed and large amounts of carbon dioxide is generates in its manufacture process. Currently, the emission factor of carbon dioxide in Brazil it is about 1344,82 lb CO2/ton manufactured cement. Producing, only in 2017, more than 10 million tonnes of CO2. As an alternative to decrease the energetic consumption and gas emission, it uses pozzolana material merged to cement, which result to technologic, economic and ecological benefits. In this study, sugarcane bagasse ash was used as a pozzolana composites to the Portland cement base, reinforced by short sisal fibers randomly distributed. It aims to determine the ideal Portland cement replacement dosage by sugarcane bagasse ash paste. Intending the least calcium hydroxide production as possible and scrutinize the influence of sugarcane bagasse ash and sisal fibers to the composites strengths. Portland cement was replaced by 5%, 10% and 15% level of sugarcane bagasse ash paste and this paste was produced determining the water/material cementing factor ideal to reach the normal consistency index. These pastes were tested by Scanning Electron Microscopy (SEM), Thermogravimetry and Derivative Thermogravimetry (TG/DTG), Isothermal Calorimetry and Compressive Strength. Composite cementitious matrix boards were reinforced by sisal fibers, with and without sugarcane bagasse ash paste at the production process and both boards were ruptured through a flexural strength test in 28 days after 10 wetting and drying cycles. Sugarcane bagasse ash presented fine grain size and that increasing the amount of sugarcane bagasse ash into the paste, the amount of water must also be increased to maintain the consistency. The paste, with 5% level of sugarcane bagasse ash, maintained the compressive strengths and decreased 30% of calcium hydroxide in 28 days. Strain-softening behavior was presented by the composites and the same 5% level of sugarcane bagasse ash replaced maintained the maximum resistant strength analysis compared to standard reference.